Kajian Pelaksanaan Dana Alokasi Khusus Bidang Pendidikan - JM Tedjawati (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this analys is to obtain information about the implementation of Special Allocation Fund (DAK) in education, in: 1) Mechanism DAK planning of Local Government; 2) channeling mechanism of DAK from Local Government; 3) Realization of DAK; 4) Implementation of monitoring and evaluation; and 5) The opinion on the administration of the DAK. The findings of this analysis are: 1) The procedure of planning implementation of DAK has made education service districts/cities in accordance with the provision of technical guidance; 2) The distribution of DAK in accordance with the procedure through three stages; 3) In some districts/cities in 2010 the implementation of DAK experience delays because of changes in the implementation of self-managed way into the auction process; 4) Monitoring and evaluation conducted by the education office DAK district/city, but checks/audits conducted by the Inspectorate General of Ministry of National Education and the Regional Monitoring Agency (BAWASDA); 5) DAK self-managed way is considered more beneficial for the schools because of the use of DAK is more flexible than an auction company that conducted the auction winner.Â ABSTRAKTujuan dari kajian ini dimaksudkan untuk memperoleh informasi tentang pelaksanaan Dana Alokasi Khusus (DAK) bidang pendidikan, dalam hal: 1) Mekanisme perencanaan DAK dari Pemerintah Daerah; 2) Mekanisme penyaluran DAK dari Pemerintah Daerah; 3) Realisasi DAK; 4) Pelaksanaan monitoring dan evaluasi; dan 5) Pendapat daerah tentang penyelenggaraan DAK. Hasil temuan kajian ini: 1) Mekanisme perencanaan sesuai dengan ketentuan petunjuk teknis; 2) Mekanisme penyaluran DAK sesuai dengan prosedur melalui tiga tahap; 3) Relaisasi pelaksanaan DAK tahun 2010 di beberapa kabupaten/kota mengalami keterlambatan karena adanya perubahan penyelenggaraan dari cara swakelola menjadi proses lelang; 4) Monitoring dan evaluasi DAK dilakukan oleh dinas pendidikan kabupaten/kota, tetapi pemeriksaan/audit dilakukan oleh Inspektorat Jenderal Kementerian Pendidikan Nasional dan Badan Pengawasan Daerah (BAWASDA); dan 5) Penyelenggaraan DAK dikelola dengan cara swakelola dianggap lebih menguntungkan bagi sekolah karena penggunaan DAK lebih luwes dibandingkan dengan lelang yang dilakukan perusahaan pemenang lelang.